Impact of blood collection tubes on thrombin generation assay results: a comparison of citrate and CTAD - Stefan Ulbing; Fabian Schäfer; Stefan Koch; Christoph Dibiasi; Marion Wiegele; Peter Quehenberger; Friederike Töpper; Eva Schaden; Johannes Gratz (Scientific Reports, 2026)
Abstract Accurate assessment of haemostasis is essential in both research and clinical practice. Thrombin generation assays (TGA) provide a comprehensive evaluation of coagulation; however, results can be influenced by preanalytical conditions, including the choice of blood collection tubes. Citrate-theophylline-adenosine-dipyridamole (CTAD) tubes are recommended by the manufacturer of the Ceveron ® alpha TGA system due to their ability to inhibit platelet activation. Nevertheless, CTAD tubes are costly, less widely available, and not manufactured in small volumes suitable for specific patient populations, such as paediatric cohorts. To evaluate whether standard citrate tubes can serve as a viable alternative, we prospectively compared TGA parameters from blood collected in 3.2% sodium citrate tubes versus CTAD tubes in 12 healthy volunteers. Assays were performed using low and high phospholipid micelle concentrations (RC low/RC high). Significant differences between citrate and CTAD were observed for all parameters with the RC low reagent. In contrast, only lag time showed significant differences with the RC high reagent. In conclusion, while citrate tubes may be used for TGA, the type of blood collection tube can influence measurements under specific assay conditions and should be considered a relevant factor when comparing and interpreting TGA results.